Synagogue as Infrastructure in Everyday Life of Batumi Jewish Community - Abakelia, Nino (Journal of religion in Europe, 2021)
The subject under scrutiny is Sephardic and Ashkenazi synagogues in Batumi (the Black Sea Region of Georgia) that reveal both universal and culturally specific forms. The paper is based on ethnographic data gathered during fieldwork in Batumi, in 2019, and on the theoretical postulates of anthropology of infrastructure. The article argues that the Batumi synagogues could be viewed and understood as ‘infrastructure’ in their own right, as they serve as objects through which other objects, people, and ideas operate and function as a system. The paper attempts to demonstrate how the sacred edifices change their trajectory according to modern conditions and how the sacred place is inserted and coexists inside a network of touristic infrastructure.